PENGARUH PENGGUNAAN BLENDED LEARNING BERBASIS SCHOOLOGY TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI HIDROLISIS GARAM - Suci Pratiwi; Lazulva (UIR Press, 2021)
This research aimed at increasing student learning achievement on Ion and pH Saline Solution Equilibrium lesson by using Schoology blanded Learninglearning model. Qualitative method was used in this research with quasi- experimental research design. All the eleventh-grade students of Natural Science of State Senior High School 1 TapungHilir in the Academic Year of 2018/2019 were the population of this research, and the samples were the eleventh-grade students of Natural Science 1 as the experimental group and the students of Natural Science 2 as the control group. Pretest-posttest control group design was used in this research. Sampling was done by using random technique. Analyzing the data was using one-way ANOVA. The data were analyzed by using inferential statistic with the help of SPSS 16.0 software. The results of calculating the data showed that the score of Sig. was lower than α, the significance score was 0.003. It showed that the learning achievement mean on Ion and pH Saline Solution Equilibrium lesson was increasing through the use of Schoology based Blended Learning. It could be concluded that there was an effect of using Schoology- based Blended Learning toward student learning achievement on Ion and pH Saline Solution Equilibrium lesson.